Proceedings of the 15th International Conference on Availability, Reliability and Security 2020
DOI: 10.1145/3407023.3407057
|View full text |Cite
|
Sign up to set email alerts
|

How do app vendors respond to subject access requests? A longitudinal privacy study on iOS and Android Apps

Abstract: EU data protection laws grant consumers the right to access the personal data that companies hold about them. In a first-of-itskind longitudinal study, we examine how service providers have complied with subject access requests over four years. In three iterations between 2015 and 2019, we sent subject access requests to vendors of 225 mobile apps popular in Germany. Throughout the iterations, 19 to 26 % of the vendors were unreachable or did not reply at all. Our subject access requests were fulfilled in 15 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…When we followed up with a comparison of the address stated in their privacy policy and our tracking number, they proceeded to completely remove the personal data of the subject without consent, acting as if no data from the subject was available. This type of reaction is not new and is in line with prior studies [12]. Later, we discovered that some translations of the privacy policy of Ret_I had a different postal code, resulting in the letter potentially being delivered to the wrong address.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…When we followed up with a comparison of the address stated in their privacy policy and our tracking number, they proceeded to completely remove the personal data of the subject without consent, acting as if no data from the subject was available. This type of reaction is not new and is in line with prior studies [12]. Later, we discovered that some translations of the privacy policy of Ret_I had a different postal code, resulting in the letter potentially being delivered to the wrong address.…”
Section: Resultssupporting
confidence: 87%
“…Finally, Kröger et al [12] observed the GDPR SAR policies of 225 mobile app developers over a longer period of time and point out numerous deceptive state-ments from developers along with general findings on inadequate data processing practices of some DCs. A similar study is being conducted related to the recent CCPA [19].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these rights aims to raise the bargaining power of consumers in digital markets [18] and to increase consumers' informational self-determination in comparison to pre-GDPR privacy laws. Regrettably, prior work [19][20][21][22] demonstrated -on the basis of a previous Californian privacy law -that corporations frequently ignored or declined requests of individuals for information access or corporate information sharing practices. As such, the RtDP -and especially its subright of direct data transfer between providers -represents the right with the highest potential economic implications only if it is applied correctly [9].…”
Section: Data Portability In Privacy Legislation and In Practicementioning
confidence: 99%
“…For data subjects, being able to answer the question "who knows what about me?" is a necessary precondition for exercising other data protection rights (e. g., data rectification, erasure, restriction of processing) in an informed manner [39]. The widespread lack of understanding of how personal data can be collected, inferred, and misused calls into question the notion of "informed consent" and may warrant some form of paternalistic government intervention.…”
Section: Regulatory Implicationsmentioning
confidence: 99%